Diversity and assemblage of vascular epiphytes in mangrove forests along the Carigara Bay in Leyte, the Philippines - Decena, Syrus Cesar Pacle (Philippine Journal of Science, 2025)
Vascular epiphyte communities associated with mangrove forests in the tropics are poorly studied. This paper presents an ecological investigation of vascular epiphytes in the mangrove forests along the Carigara Bay in Leyte, the Philippines, by comparing the diversity (abundance, species richness, and Shannon-Wiener) between mangrove forest types (fringe and riverine), mangrove forest zones (landward, middleward, and seaward or along the water), and tree height zones (basal, trunk, and canopy). In addition, variations in species composition, environmental variables that could influence diversity patterns, and host affinity were examined. Vascular epiphyte communities were sampled in all host trees inside the six 7-m radius circular plots demarcated at 25-m intervals along a 125-m length transect line laid in each zone of mangrove stands. A total of 23 vascular epiphyte species that belong to six families were documented in the mangrove forests – with Davallia solida, Drynaria quercifolia, Dendrobium crumenatum, Hoya merrillii, and Pyrrosia lanceolata as some of the most abundant species. The vascular epiphyte abundance and species richness were found to be significantly higher in both middleward and seaward or along water. All the diversity indices of epiphytes were significantly higher in the canopy. Moreover, fringe mangrove forests were associated with fewer vascular epiphytes – which include Davallia solida, Dendrobium crumenatum, Drynaria quercifolia, Luisia tristis, and Micropera sp., whereas the riverine mangrove forests were associated with all the rest of the remaining species such as Hoya merrillii and Pyrrosia lanceolata as the most abundant species. The increasing vascular epiphyte diversity pattern was explained by the increasing host tree height, canopy cover, and distance to sea/river. In contrast, the reduction in diversity was explained by increasing light intensity. The indicator species analysis revealed that six out of 23 vascular epiphyte species served as indicator species for mangrove trees. Lastly, it is imperative to protect the mangrove forests of the bay to ensure the continued persistence and diversity of the associated vascular epiphyte communities.